Pengaruh Promosi Kesehatan Berperilaku “Patuh” Menggunakan Leaflet Terhadap Motivasi Dan Upaya Pengendalian Hipertensi - Wirawati; Yusriani; Mansyur Sulolipu (Pusat Kajian dan Pengelolaan Jurnal FKM UMI, 2026)
Hypertension is a significant health problem in the world due to its high prevalence rate and is associated with an increased risk of cardiovascular disease. The increased risk of hypertension is due to a lack of knowledge in hypertension management, causing sufferers to come to health facilities when there are complaints or even when the condition is already severe, such as difficulty in lowering blood pressure or complications such as stroke and kidney failure. This study aims to determine the effect of health promotion behavior